1990
DOI: 10.1111/j.1365-2826.1990.tb00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Kappa‐Opioid Receptor Involvement in the Regulation of Pulsatile Luteinizing Hormone Release During Early Pregnancy in the Rat

Abstract: The object of this study was to gain further insight into endogenous opioid peptide suppression of pulsatile luteinizing hormone (LH) release in early gestation in the rat by examining whether selective blockade of mu-, delta-, or kappa-opioid receptor(s) results in stimulation of pulsatile LH secretion at this time. Previous reports demonstrated stimulation of pulsatile LH release during early gestation by intravenous infusions of naloxone, an endogenous opioid peptide receptor antagonist whose binding is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 45 publications
(27 reference statements)
2
19
0
Order By: Relevance
“…Dyn has long been known to decrease GnRH pulse frequency [34], and its primary role as such has been postulated to be in mediating the negative feedback effects of progesterone (P 4 ) on the neuroendocrine hypothalamus [35]. The κ-opioid receptor (KOR), through which Dyn preferentially signals [36], is not abundantly expressed in the vicinity of GnRH neurones [37,38].…”
Section: Mechanisms Of Kndy Signallingmentioning
confidence: 99%
“…Dyn has long been known to decrease GnRH pulse frequency [34], and its primary role as such has been postulated to be in mediating the negative feedback effects of progesterone (P 4 ) on the neuroendocrine hypothalamus [35]. The κ-opioid receptor (KOR), through which Dyn preferentially signals [36], is not abundantly expressed in the vicinity of GnRH neurones [37,38].…”
Section: Mechanisms Of Kndy Signallingmentioning
confidence: 99%
“…MUA volleys in kisspeptin/metastin neurons are inhibited by Dyn, which results in a decrease in gonadotropin release [41,42]. We expected Dyn to exert inhibitory effects on pituitary gonadotrophs and lactotrophs because these cells, like kisspeptin/metastin neurons, express the Dyn receptor, KOR.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…Dynorphin-KOR signaling is considered to be involved in the suppression of GnRH/LH pulses, because central administration of nor-binaltorphimine (nor-BNI), a selective KOR antagonist, increases the amplitude and frequency of LH pulses during early pregnancy [23] and the mean LH level and LH pulse frequency during midpregnancy [24] in rats. Further, Goodman et al [25] suggested that the central Dyn-KOR system mediates progesterone negative feedback on GnRH/LH pulses in ewes.…”
mentioning
confidence: 99%